Couples Living with HIV: Men's Reproductive Intentions, Practices, and Attitudes. (March 2017) - Rodriguez, Violeta J.; Spence, Andrew; Monda, Mallory; Potter, JoNell; Jones, Deborah
Background: Desires to have children are not lessened by a woman's HIV status. Couples may lack information to conceive safely, and men may be especially uninformed. This study examined reproductive intentions, practices, and attitudes among men in HIV-infected couples, including attitudes regarding the perceived risk of vertical and horizontal transmission, safer conception, and preconception planning. Methods: Men ( n = 12) in HIV-infected couples were interviewed regarding reproductive intentions, attitudes, and knowledge and qualitative assessments were coded for dominant themes. Results: Themes primarily addressed concerns about the health of the baby, men's involvement in pregnancy, safer conception, concerns about HIV transmission and antiretroviral therapy, and HIV infection. Men lacked information on safer conception and newer HIV prevention strategies, such as pre-exposure prophylaxis (PrEP). Discussion: Gaps in knowledge regarding preconception practices among men in HIV-infected couples were identified. Results highlight men's desire for involvement in preconception planning, and opportunities for providers to facilitate this practice and to increase patient education and the use of PrEP are discussed.